Molecular Characterization of Morphologically Similar Four Pieridae Butterflies (Lepidoptera: Insecta) by RAPD-PCR Technique - ASHISH D. TIPLE; SONALI V. PADWAD; VISHAL P. DESHMUKH (International Journal of Pharma and Bio Sciences, 2010)
Molecular characterization of four morphologically similar Pieridae butterflies was carried out using RAPD markers. Total 121 bands were scored with 8 decamer primers, of which 115 were polymorphic while 6 were monomorphic and the percentage of polymorphism was 95.04%. Dendrogram based on average similarity coefficient of 08 primers grouped four Pieridae species into two distinct clusters. Cluster-I comprised of 3 species viz. Eurema laeta, E. hecabe and E. blanda, while cluster-II consisted of E. andersonii. Cluster-I further subdivided into two sub-clusters, sub-cluster-I consisting of only Eurema laeta and sub-cluster-II comprised of E. hecabe and E. blanda. Genetic similarities between these four species were discussed on the basis of morphological characters and RAPD data.